Cyclin-dependent kinase 4 and 6 inhibitors for hormone receptor-positive breast cancer: past, present, and future. Issue 10226 (7th March 2020) - Spring, Laura M; Wander, Seth A; Andre, Fabrice; Moy, Beverly; Turner, Nicholas C; Bardia, Aditya
Summary: The development and approval of cyclin-dependent kinase (CDK) 4 and 6 inhibitors for hormone receptor-positive and human epidermal growth factor receptor 2 (HER2)-negative metastatic breast cancer represents a major milestone in cancer therapeutics. Three different oral CDK4/6 inhibitors, palbociclib, ribociclib, and abemaciclib, have significantly improved progression-free survival by a number of months when combined with endocrine therapy. More recently, improvement in overall survival has been reported with ribociclib and abemaciclib. The toxicity profile of all three drugs is well described and generally easily manageable with dose reductions when indicated. More myelotoxicity is observed with palbociclib and ribociclib, but more gastrointestinal toxicity is observed with abemaciclib. Emerging data is shedding light on the resistance mechanisms associated with CDK4/6 inhibitors, including cell cycle alterations and activation of upstream tyrosine kinase receptors. A number of clinical trials are exploring several important questions regarding treatment sequencing, combinatorial strategies, and the use of CDK4/6 inhibitors in the adjuvant and neoadjuvant settings, thereby further expanding and refining the clinical application of CDK4/6 inhibitors for patients with breast cancer.